1989
DOI: 10.1161/01.hyp.14.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of hypertension in rats by cross circulation.

Abstract: Cross circulation was performed in 54 couples of spontaneously hypertensive and normotensive rats. Blood was pumped through two anastomoses between the carotid arteries and external jugular veins in both directions with equal flow rate. In normotensive rats cross-circulated with untreated spontaneously hypertensive rats mean arterial pressure increased by 20.9±12.2 mm Hg (p<0.01). Administration of digoxin antibody in a dose binding 0.25 mg digoxin to the spontaneously hypertensive rats before cross circulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…All experiments were carried out using rat thoracic aortas isolated from 6-month-old male spontaneously hypertensive rats (SHR) of the Münster strain (weight 300-400 g. systolic blood pressure 195 ± 4 mm Hg, mean ± SEM) as previously described [12] and agematched male normotensive Wistar-Kyoto rats (WKY, systolic blood pressure 116+3 mm Hg). Vascular smooth muscle cells (VSMC) were cultured according to previously described methods [13,14], Briefly, cells were incubated in Dulbecco's modified Eagle medium (Gibco.…”
Section: Cell Culturementioning
confidence: 99%
“…All experiments were carried out using rat thoracic aortas isolated from 6-month-old male spontaneously hypertensive rats (SHR) of the Münster strain (weight 300-400 g. systolic blood pressure 195 ± 4 mm Hg, mean ± SEM) as previously described [12] and agematched male normotensive Wistar-Kyoto rats (WKY, systolic blood pressure 116+3 mm Hg). Vascular smooth muscle cells (VSMC) were cultured according to previously described methods [13,14], Briefly, cells were incubated in Dulbecco's modified Eagle medium (Gibco.…”
Section: Cell Culturementioning
confidence: 99%
“…In spontaneously hypertensive rats, parabiosis experiments [2,3] and, more recently, crosscirculation studies [4] also suggested a circulating pressor sive factor in spontaneously hypertensive rats. Similarly, in plasma of essential hypertensives, a vasopressor frac tion could be identified by intravenous injection in rats [10].…”
Section: Introductionmentioning
confidence: 99%
“…SHR from the Munster strain as previously described 15 and the normotensive WistarKyoto (WKY) control strain were obtained from Medizinische Poliklinik, Munster, Germany. The rats were fed a standard pellet diet and allowed tap water ad libitum.…”
Section: Methodsmentioning
confidence: 99%